Copper-nickel-based catalyst alloy descaling material and preparation method thereof

Through the descaling material of copper-nickel-based catalyst alloy, the element ratio is used to change the potential difference of calcium and magnesium ions, and the scale reaction speed is accelerated, which solves the problem of scale blockage in shower equipment, and achieves efficient descaling and corrosion resistance, while avoiding the use of high-quality descaling and corrosion resistance. It is suitable for industrial production.

CN119194157APending Publication Date: 2024-12-27AQUAMATE SANITARY WARE EURO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411371522.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing scale-resistant materials contain Pb, V and other substances that are harmful to the human body, and foreign matters are generated after corrosion in water, making it difficult to effectively prevent the shower equipment from being blocked due to scale.

Method used

Using copper-nickel-based catalyst alloy descaling material, by controlling the ratio of Cu, Ni, Zn, Ag, Fe, Mn and other elements, an alloy with excellent descaling and corrosion resistance is formed, and the potential of calcium and magnesium ions is changed by micro current. Poor, speed up the chemical reaction of scale, prevent accumulation, and avoid the use of harmful materials during the preparation process.

Benefits of technology

It realizes the formation of scale crystals and discharged at a lower concentration, prevents accumulation, improves the service life and health and safety of the equipment, and the preparation method is simple to operate and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of alloys, in particular to a copper-nickel-based catalyst alloy descaling material and a preparation method thereof. The copper-nickel-based catalyst alloy descaling material comprises the following raw materials in percentage by weight: 40%-60% of Cu, 20%-30% of Ni, 5%-15% of Zn, 5%-20% of Sn, 0.5%-5% of Ag, 0.1%-5% of Fe and 0.05%-5% of Mn. The copper-nickel catalyst alloy has excellent descaling and corrosion-resistant properties, so that the static electromotive force of the contacted fluid is changed, the static potential of the fluid is changed through the catalyst material, the fluid is polarized, the chemical reaction speed of scale in the fluid is accelerated, and calcium and magnesium ions can form scale crystals at lower concentration and are discharged along with the fluid; and accumulation is prevented. In the preparation process of the descaling material, materials such as Pb, Sb and V which are harmful to human bodies are not added, so that the descaling material is healthy and environment-friendly; the preparation method is convenient to operate and control, high in production efficiency and beneficial to industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of alloys, and in particular to a copper-nickel based catalyst alloy descaling material and a preparation method thereof. Background Art

[0002] In industrial production and people's daily life, scaling often occurs in products and pipelines, which not only easily causes many adverse consequences such as equipment blockage and damage, affecting the normal operation of the equipment, but also long-term drinking of water with high hardness will cause adverse damage to the body.

[0003] At present, showerheads have been widely used in people's lives. During the long-term use of showerheads, the water outlet is clogged due to scale problems, affecting the shower experience and the life of the showerhead. Scale is mainly a precipitate formed by the combination of calcium and magnesium ions and carbonate ions in water. The scale-inhibiting materials on the market are currently used for industrial purposes. The content of Pb and V and other harmful substances to the human body is too high, and it is easy to be corroded by water to generate foreign matter, which needs to be solved. Summary of the invention

[0004] In order to solve the deficiencies of the above-mentioned prior art, the purpose of the present invention is to provide a copper-nickel-based catalyst alloy descaling material and a preparation method thereof, wherein the copper-nickel catalyst alloy has excellent descaling and corrosion resistance, changes the electrostatic potential of the contacted fluid, changes the electrostatic potential of the fluid through the catalyst material, causes the fluid to produce polarization, accelerates the speed of the chemical reaction of scale formation in the fluid, and allows calcium and magnesium ions to form scale crystals at a lower concentration and be discharged with the fluid to prevent accumulation. During the production process of the descaling material, no materials such as Pb, Sb, and V that are harmful to the human body are added, which is healthy and environmentally friendly; the preparation method thereof is easy to operate and control, has high production efficiency, and is conducive to industrial production.

[0005] The object of the present invention is achieved through the following technical scheme: a copper-nickel based catalyst alloy descaling material, comprising the following raw materials in weight percentage: Cu 40-60%, Ni 20-30%, Zn 5-15%, Sn 5-20%, Ag 0.5-5%, Fe 0.1-5%, Mn 0.05-5%.

[0006] The copper-nickel-based catalyst alloy descaling material of the present invention is prepared by combining raw materials such as Cu, Ni, Zn, Ag, Fe, and Mn, and controlling the dosage ratio of each raw material to obtain a copper-nickel catalyst alloy with excellent descaling performance and corrosion resistance. Among them, the alloy descaling material is based on Cu and Ni elements, which helps to ensure the corrosion resistance of the catalyst alloy. Ag and Sn elements enhance the corrosion resistance, improve the service life, and prevent the alloy itself from oxidizing and precipitating harmful substances; Zn and Ag are both electronegative elements. Under the impact and friction of water flow, they spontaneously release free electrons to form microcurrents, change the potential difference of calcium and magnesium ions, and make them lose the scaling conditions; trace amounts of Fe, Mn and other elements are used for alloy strengthening and grain refinement.

[0007] Furthermore, the copper-nickel based catalyst alloy descaling material comprises the following raw materials in weight percentage: Cu 50-58%, Ni 22-24%, Zn 10-12%, Sn 5-8%, Ag 1-1.2%, Fe 3-3.8%, and Mn 0.1-2%.

[0008] Furthermore, the copper-nickel based catalyst alloy descaling material comprises the following raw materials in weight percentage: Cu 50%, Ni 24%, Zn 12%, Sn 8%, Ag 1.2%, Fe 3.8%, and Mn 1%.

[0009] Furthermore, the copper-nickel based catalyst alloy descaling material is characterized by comprising the following raw materials in weight percentage: Cu 58%, Ni 22%, Zn 10%, Sn 5%, Ag 1%, Fe 3%, and Mn 1%.

[0010] The present invention also provides a method for preparing a copper-nickel based catalyst alloy descaling material, comprising the following steps: (1) According to the raw material ratio of the alloy descaling material, copper material, Cu-Ni master alloy, Cu-Fe master alloy, Cu-Mn master alloy, silver material, zinc material and tin material are taken; (2) mixing the copper material, the Cu-Ni master alloy, the Cu-Fe master alloy, and the Cu-Mn master alloy and performing a heating and melting treatment until the copper material, the Cu-Ni master alloy, the Cu-Fe master alloy, and the Cu-Mn master alloy are all melted to obtain a molten metal A; (3) Adding silver, zinc and tin to molten metal A, heating and melting the mixture, and stirring the mixture until the silver, zinc and tin are completely melted to obtain molten metal B; (4) After removing the scum from the molten metal B, the molten metal B is injected into a mold to form a metal ingot, which is then cooled and taken out; (5) Processing the obtained metal ingot into a descaling material of a desired shape.

[0011] Furthermore, in step (1), in the Cu-Ni master alloy, the mass ratio of Cu to Ni is 3-4:6-7; in the Cu-Fe master alloy, the mass ratio of Cu to Fe is 17-19:1-3; in the Cu-Mn master alloy, the mass ratio of Cu to Mn is 13-15:5-7.

[0012] Furthermore, in step (2), the copper material, the Cu-Ni master alloy, the Cu-Fe master alloy, and the Cu-Mn master alloy are mixed and placed in an induction furnace, and the temperature is raised to 1100-1350° C. until the copper material, the Cu-Ni master alloy, the Cu-Fe master alloy, and the Cu-Mn master alloy are all melted.

[0013] Furthermore, in step (3), the furnace is heated to 1050-1200° C., silver material, zinc material and tin material are added, and stirred thoroughly until they are completely melted.

[0014] Furthermore, in step (4), the metal ingot is cooled to room temperature by water cooling.

[0015] In the preparation method of the copper-nickel-based catalyst alloy descaling material of the present invention, the alloy composition is optimized, and the specific steps and parameters of the preparation process are designed. At the same time, Ni, Fe, and Mn are respectively combined with part of Cu to form an intermediate alloy, so that the addition amount of Ni, Fe, and Mn is accurately controlled, and the intermediate alloy has a lower melting point and a faster dissolution rate, which solves the problems that some metal elements in the system are easy to burn and high melting points are difficult to melt. The present invention can strengthen the alloy and improve the grain refinement effect by adopting the above method, which is helpful to improve the performance of the alloy descaling material. The alloy descaling material product has a low impurity content and does not contain materials such as Pb, Sb, and V that are harmful to the human body.

[0016] The beneficial effects of the present invention are as follows: the copper-nickel catalyst alloy of the present invention has excellent descaling and corrosion resistance, changes the electrostatic potential of the fluid in contact, changes the electrostatic potential of the fluid through the catalyst material, causes the fluid to produce polarization, accelerates the speed of chemical reaction of scale formation in the fluid, and allows calcium and magnesium ions to form scale crystals at a relatively low concentration and be discharged with the fluid to prevent accumulation. During the production process of the descaling material, no materials such as Pb, Sb, and V that are harmful to the human body are added, which is healthy and environmentally friendly; the preparation method thereof is easy to operate and control, has high production efficiency, and is conducive to industrial production. DETAILED DESCRIPTION

[0017] In order to facilitate the understanding of those skilled in the art, the present invention is further described below in conjunction with embodiments, and the contents mentioned in the implementation modes are not intended to limit the present invention.

[0018] In some embodiments of the present invention, a copper-nickel based catalyst alloy descaling material comprises the following raw materials in weight percentage: Cu (copper) 40-60%, Ni (nickel) 20-30%, Zn (zinc) 5-15%, Sn (tin) 5-20%, Ag (silver) 0.5-5%, Fe (iron) 0.1-5%, and Mn (manganese) 0.05-5%.

[0019] In some embodiments of the present invention, a copper-nickel based catalyst alloy descaling material comprises the following raw materials in weight percentage: Cu 50-58%, Ni 22-24%, Zn 10-12%, Sn 5-8%, Ag 1-1.2%, Fe 3-3.8%, and Mn 0.1-2%.

[0020] In one embodiment of the present invention, a copper-nickel based catalyst alloy descaling material includes the following raw materials in weight percentage: Cu 60%, Ni 21%, Zn 9%, Sn 5%, Ag 1%, Fe 3%, and Mn 1%.

[0021] In one embodiment of the present invention, a copper-nickel based catalyst alloy descaling material includes the following raw materials in weight percentage: Cu 52%, Ni 23%, Zn 11%, Sn 7%, Ag 1.2%, Fe 3.8%, and Mn 2%.

[0022] In some embodiments of the present invention, a method for preparing a copper-nickel based catalyst alloy descaling material comprises the following steps: (1) According to the raw material ratio of the alloy descaling material, copper ingots, Cu-Ni master alloy, Cu-Fe master alloy, Cu-Mn master alloy, silver ingots, zinc ingots and tin particles are taken; (2) The copper ingot, the Cu-Ni master alloy, the Cu-Fe master alloy, and the Cu-Mn master alloy are mixed and heated and melted until the copper ingot, the Cu-Ni master alloy, the Cu-Fe master alloy, and the Cu-Mn master alloy are all melted to obtain a molten metal A; the purity of the copper ingot is above 99.9%; (3) Adding silver ingots, zinc ingots and tin particles to molten metal A for heating and melting, stirring until the silver, zinc and tin materials are completely melted, thereby obtaining molten metal B; (4) After removing the scum from the molten metal B, the molten metal B is injected into a mold to form a metal ingot, which is then cooled and taken out; (5) Processing the obtained metal ingot into a descaling material of a desired shape.

[0023] In some embodiments of the present invention, in step (1), in the Cu-Ni master alloy, the mass ratio of Cu to Ni is 3-4:6-7; in the Cu-Fe master alloy, the mass ratio of Cu to Fe is 17-19:1-3; in the Cu-Mn master alloy, the mass ratio of Cu to Mn is 13-15:5-7.

[0024] In some embodiments of the present invention, in step (2), the copper ingot, the Cu-Ni master alloy, the Cu-Fe master alloy, and the Cu-Mn master alloy are mixed and placed in an induction furnace, and the temperature is raised to 1100-1350° C. until the copper ingot, the Cu-Ni master alloy, the Cu-Fe master alloy, and the Cu-Mn master alloy are completely melted.

[0025] In some embodiments of the present invention, in step (3), the furnace is heated to 1050-1200° C., and silver ingots, zinc ingots and tin particles are added in sequence and stirred thoroughly until they are completely melted.

[0026] In some embodiments of the present invention, in step (4), the metal ingot is cooled to room temperature by water cooling.

[0027] Example 1 In this embodiment, a copper-nickel based catalyst alloy descaling material includes the following raw materials in weight percentage: Cu 50%, Ni 24%, Zn 12%, Sn 8%, Ag 1.2%, Fe 3.8%, and Mn 1%.

[0028] In this embodiment, a method for preparing a copper-nickel based catalyst alloy descaling material comprises the following steps: (1) According to the raw material ratio of the alloy descaling material, copper ingots, Cu-Ni master alloy, Cu-Fe master alloy, Cu-Mn master alloy, silver ingots, zinc ingots and tin particles are taken; (2) mixing the copper ingot, the Cu-Ni master alloy, the Cu-Fe master alloy, and the Cu-Mn master alloy and performing a heating and melting treatment until the copper ingot, the Cu-Ni master alloy, the Cu-Fe master alloy, and the Cu-Mn master alloy are all melted to obtain a molten metal A; (3) Open the furnace and heat it to 1100°C. Add silver ingots, zinc ingots and tin particles to the molten metal A in sequence and stir until the silver, zinc and tin materials are completely melted to obtain molten metal B. (4) After removing the scum from the molten metal B, the molten metal B is poured into a mold to form a metal ingot, which is then cooled to room temperature with water and the metal ingot is taken out; (5) Processing the obtained metal ingot into a descaling material of a desired shape.

[0029] Furthermore, in step (1), in the Cu-Ni master alloy, the mass ratio of Cu to Ni is 37:63; in the Cu-Fe master alloy, the mass ratio of Cu to Fe is 9:1; and in the Cu-Mn master alloy, the mass ratio of Cu to Mn is 7:3.

[0030] Furthermore, in step (2), the copper ingot, the Cu-Ni master alloy, the Cu-Fe master alloy, and the Cu-Mn master alloy are mixed and placed in an induction furnace, and the temperature is raised to 1150° C. until the copper ingot, the Cu-Ni master alloy, the Cu-Fe master alloy, and the Cu-Mn master alloy are completely melted.

[0031] Example 2 In this embodiment, the copper-nickel based catalyst alloy descaling material includes the following raw materials in weight percentage: Cu 58%, Ni 22%, Zn 10%, Sn 5%, Ag 1%, Fe 3%, and Mn 1%.

[0032] This embodiment also provides a method for preparing the copper-nickel based catalyst alloy descaling material, comprising the following steps: (1) According to the raw material ratio of the alloy descaling material, copper ingots, Cu-Ni master alloy, Cu-Fe master alloy, Cu-Mn master alloy, silver ingots, zinc ingots and tin particles are taken; (2) mixing the copper ingot, the Cu-Ni master alloy, the Cu-Fe master alloy, and the Cu-Mn master alloy and performing a heating and melting treatment until the copper ingot, the Cu-Ni master alloy, the Cu-Fe master alloy, and the Cu-Mn master alloy are all melted to obtain a molten metal A; (3) Open the furnace and heat it to 1200°C. Add silver ingots, zinc ingots and tin particles to the molten metal A in sequence and stir until the silver, zinc and tin materials are completely melted to obtain molten metal B. (4) After removing the scum from the molten metal B, the molten metal B is poured into a mold to form a metal ingot, which is then cooled to room temperature with water and the metal ingot is taken out; (5) Processing the obtained metal ingot into a descaling material of a desired shape.

[0033] Furthermore, in step (1), in the Cu-Ni master alloy, the mass ratio of Cu to Ni is 37:63; in the Cu-Fe master alloy, the mass ratio of Cu to Fe is 9:1; and in the Cu-Mn master alloy, the mass ratio of Cu to Mn is 7:3.

[0034] Furthermore, in step (2), the copper ingot, the Cu-Ni master alloy, the Cu-Fe master alloy, and the Cu-Mn master alloy are mixed and placed in an induction furnace, and the temperature is raised to 1250° C. until the copper ingot, the Cu-Ni master alloy, the Cu-Fe master alloy, and the Cu-Mn master alloy are completely melted.

[0035] The scale inhibition performance of Examples 1-2 was tested, and the test method was as follows: first, an experimental group was set up, 50L of 1g / L calcium chloride aqueous solution was added to the water tank of the water tester, and a water pump was used to connect the scale inhibition material product of Examples 1-2 for water circulation, and the flow rate was set to 8L / min; a stainless steel pipe with a diameter of 20mm and a length of 200mm was weighed and recorded, and then connected to the circulating water circuit, the water tank was heated in a water bath, and the temperature was constant at 80°C. The water tester was turned on and circulated for 120h. During this period, the water tank was regularly replenished with water, and the water volume was always kept at 50L; after 168h, the stainless steel pipe was removed, dried and weighed; another control group was set up. Except that the scale inhibition product was not connected, the rest of the devices, parameters, and steps were the same as the experimental group, and the weight increase of the hanging piece was calculated in the same way; the scale inhibition rate was calculated as (weight gain of the control group-weight gain of the experimental group) / weight gain of the control group*100%.

[0036] By testing the copper-nickel catalyst alloy descaling materials of Examples 1-2 according to the weight gain test method, it can be found that the scale inhibition rate of Example 1 is more than 80%, and the scale inhibition rate of Example 2 is more than 75%, showing excellent descaling performance. The copper-nickel catalyst alloy of the present invention has excellent descaling and corrosion resistance, which changes the electrostatic potential of the fluid in contact, changes the electrostatic potential of the fluid through the catalyst material, causes the fluid to produce polarization, accelerates the speed of chemical reaction of scale formation in the fluid, and allows calcium and magnesium ions to form scale crystals at a relatively low concentration and be discharged with the fluid to prevent accumulation. During the production process of the descaling material, no materials such as Pb, Sb, and V that are harmful to the human body are added, which is healthy and environmentally friendly; the copper-nickel catalyst alloy descaling material is not easily corroded in liquids such as calcium chloride aqueous solution, and has good corrosion resistance.

[0037] The above specific embodiments are further explanations of the technical solutions and beneficial effects of the present invention, and are not limitations of the implementation methods. For those skilled in the art, any obvious replacements that do not depart from the concept of the present invention are within the protection scope of the present invention.

Claims

1. A copper-nickel based catalyst alloy descaling material, characterized in that: The raw materials include the following weight percentages: Cu 40-60%, Ni 20-30%, Zn 5-15%, Sn 5-20%, Ag 0.5-5%, Fe 0.1-5%, and Mn 0.05-5%.

2. The copper-nickel based catalyst alloy descaling material according to claim 1, characterized in that: The invention comprises the following raw materials in weight percentage: Cu 50-58%, Ni 22-24%, Zn10-12%, Sn 5-8%, Ag 1-1.2%, Fe 3-3.8%, and Mn 0.1-2%.

3. The copper-nickel based catalyst alloy descaling material according to claim 1, characterized in that: The raw materials include the following weight percentages: Cu 50%, Ni 24%, Zn 12%, Sn 8%, Ag 1.2%, Fe 3.8%, and Mn 1%.

4. The copper-nickel based catalyst alloy descaling material according to claim 1, characterized in that: The raw materials include the following weight percentages: Cu 58%, Ni 22%, Zn 10%, Sn 5%, Ag 1%, Fe 3%, and Mn 1%.

5. A method for preparing the copper-nickel based catalyst alloy descaling material according to any one of claims 1 to 4, characterized in that: The steps include: (1) According to the raw material ratio of the alloy descaling material, copper material, Cu-Ni master alloy, Cu-Fe master alloy, Cu-Mn master alloy, silver material, zinc material and tin material are taken; (2) mixing the copper material, the Cu-Ni master alloy, the Cu-Fe master alloy, and the Cu-Mn master alloy and performing a heating and melting treatment until the copper material, the Cu-Ni master alloy, the Cu-Fe master alloy, and the Cu-Mn master alloy are all melted to obtain a molten metal A; (3) Adding silver, zinc and tin to molten metal A, heating and melting the mixture, and stirring the mixture until the silver, zinc and tin are completely melted to obtain molten metal B; (4) After removing the scum from the molten metal B, the molten metal B is injected into a mold to form a metal ingot, which is then cooled and taken out; (5) Processing the obtained metal ingot into a descaling material of a desired shape.

6. The method for preparing the copper-nickel based catalyst alloy descaling material according to claim 5, characterized in that: In step (1), in the Cu-Ni master alloy, the mass ratio of Cu to Ni is 3-4:6-7.

7. The method for preparing the copper-nickel based catalyst alloy descaling material according to claim 5, characterized in that: In step (1), in the Cu-Fe master alloy, the mass ratio of Cu to Fe is 17-19:1-3; in the Cu-Mn master alloy, the mass ratio of Cu to Mn is 13-15:5-7.

8. The method for preparing the copper-nickel based catalyst alloy descaling material according to claim 5, characterized in that: In step (2), the copper material, the Cu-Ni master alloy, the Cu-Fe master alloy, and the Cu-Mn master alloy are mixed and placed in an induction furnace, and the temperature is raised to 1100-1350° C. until the copper material, the Cu-Ni master alloy, the Cu-Fe master alloy, and the Cu-Mn master alloy are completely melted.

9. The method for preparing the copper-nickel based catalyst alloy descaling material according to claim 5, characterized in that: In step (3), the furnace is heated to 1050-1200°C, silver, zinc and tin are added, and stirred thoroughly until they are completely melted.

10. The method for preparing the copper-nickel based catalyst alloy descaling material according to claim 5, characterized in that: In step (4), the metal ingot is cooled to room temperature by water cooling.